Answered

Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Given f(X) =-X+ 6 write an equation for f(x + 3).

Sagot :

Answer:

3 - x

Step-by-step explanation:

f(x) = -x + 6

f(x + 3)

Substitute (x + 3) in for x;

f(x + 3) = -(x + 3) + 6

= - x - 3 + 6

= -x + 3